1995
DOI: 10.1002/jab.770060403
|View full text |Cite
|
Sign up to set email alerts
|

Histological and mechanical comparison of hydroxyapatite‐coated cobalt‐chrome and titanium implants in the rabbit femur

Abstract: The purpose of this study was to compare hydroxyapatite (HA)-coated titanium (Ti) and HA-coated cobalt-chrome (CoCr) implants in the distal femur of the rabbit by evaluating bone apposition and interfacial shear strength. Bilateral cylindrical implants with a plasma sprayed 50-microns thick HA coating were press-fit into the metaphyseal cancellous bone of the lateral femoral condyles in a transverse fashion, and the animals were sacrificed at 2, 4, and 8 weeks postimplantation. Mechanical strength of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In recent years, numerous studies of animals have shown that a calcium hydroxyapatite coating increases bone-implant contact through the preferential deposition of new bone on the surface of the implant and the host bed, with no intervening fibrous tissue. [23][24][25] However, some studies show no significant difference in clinical results between implants with and without hydroxyapatite porous coating. 26 Thus, it is not certain that porous coating with hydroxyapatite is the best solution to the problem of bone-implant interlocking.…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, numerous studies of animals have shown that a calcium hydroxyapatite coating increases bone-implant contact through the preferential deposition of new bone on the surface of the implant and the host bed, with no intervening fibrous tissue. [23][24][25] However, some studies show no significant difference in clinical results between implants with and without hydroxyapatite porous coating. 26 Thus, it is not certain that porous coating with hydroxyapatite is the best solution to the problem of bone-implant interlocking.…”
Section: Introductionmentioning
confidence: 97%
“…Other alloys such as CoCr (8), CoCrMo (6) and stainless steels (9) are used. These metallic alloys are biocompatible but they are not able to induce bone tissue regeneration, so that, these alloys must be subjected to surface treatments to allow osteointegration (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…For bone tissue engineering, a wide choice of scaffold materials, including metals (Friedman et al, 1995), natural and synthetic polymers (Heise et al, 1990, Vitale-Brovarone et al, 2005, and glasses has been proposed (Ozawa and Kasugai, 1996), each of them presenting different mechanical, chemical, and biological characteristics. Particular attention has been given to the manufacturing of porous bioceramics that mimic trabecular bone chemistry and structure (Martinetti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%